Modified Gegen Qinlian Decoction Ameliorates DSS-Induced Colitis in Mice via the Modulation of NF-κB and Nrf2/HO-1 Pathways - Jinke Huang; Jiaqi Zhang; Zhihong Liu; Jing Ma; Yifan Wang; Fengyun Wang; Xudong Tang (Mediators of Inflammation)
Conclusion: MGQD alleviated UC by suppressing inflammation and oxidative stress via the modulation of NF-κB and Nrf2/HO-1 pathways, suggesting that MGQD may be a candidate therapy for UC.